Metal-free carbon-based quantum materials with strong room-temperature ferromagnetism and preparation methods thereof
By thermal annealing and fluorinating the high-purity g-C3N4, the heptaazine structural unit is broken and the cyano group and N-C=N bond is formed, the problems of low magnetic properties and poor stability of carbon-based ferromagnetic materials are solved, and metal-free carbon-based quantum materials with high Curie temperature and strong room temperature ferromagnetic properties are obtained, which realizes the possibility of large-scale production in industry and finds practical applications in multiple fields.
Patent Information
- Application Number
- CN202510374219.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2045-03-27
AI Technical Summary
The existing carbon-based ferromagnetic materials have problems of low magnetic properties and poor stability, and are difficult to produce on a large scale in the industry. In addition, traditional metal ferromagnetic materials consume high energy, severe carbon emissions, high raw material costs, and unstable supply.
High-purity g-C3N4 is used as raw material, and the adsorbed oxygen and structural oxygen are removed through two-step thermal annealing treatment. Then fluorinated with xenon difluoride, and thermal defluorination is carried out in argon, breaking the heptaazine structural unit, forming a cyano group and N-C=N bond, introducing N-C=N hanging bond and C-C chemical bond, generating unpaired spins, thereby enhancing ferromagnetic coupling.
The obtained metal-free carbon-based quantum materials have high Curie temperature, strong room temperature ferromagnetics, applicable high magnetization strength and good chemical stability. They can be practically used in aerospace, biomedicine, spintronics and other fields, replacing traditional metal alloys or oxide ferromagnetic materials.
Smart Images

Figure CN119873765B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of quantum information materials, and particularly relates to a metal-free carbon-based quantum material with strong room-temperature ferromagnetism and a preparation method thereof. Background Art
[0002] Traditional metal ferromagnetic materials, such as iron (Fe), cobalt (Co), nickel (Ni), etc., form the basis of modern industry, electronics and energy fields. Their magnetism comes from the spin and exchange interaction of 3d electrons, and the arrangement of magnetic domains can be finely regulated by an external magnetic field. However, traditional ferromagnetic metal materials face a series of defects that cannot be ignored in actual production and application. For example, their preparation process has high energy consumption and serious carbon emissions, which does not conform to the current industrial trend of green and low-carbon development; at the same time, they have a strong dependence on rare metals, with high raw material costs and unstable supply; in addition, high-temperature melting and complex heat treatment processes not only increase production costs but also are accompanied by a large amount of environmental pollution. In this context, carbon-based ferromagnetic materials have become an important development direction for solving the above problems due to their unique structure and properties. Carbon materials such as graphene, carbon nanotubes, diamond-like carbon films (DLC), etc. have low density, high specific strength, excellent chemical stability and biocompatibility, and at the same time are rich in resources and environmentally friendly, and have important research and application value in the new generation of electronics and sensing technologies. However, existing carbon-based ferromagnetic materials have the disadvantages of low magnetic performance and poor stability, making it difficult to be mass-produced in industry.
[0003] Yong Wang et al. (Yong Wang, Yilv Guo, Zhaokun Wang, Lin Fu, Yu Zhang, Yongjie Xu, Shijun Yuan, Hongzhe Pan, Youwei Du, Jinlan Wang, and Nujiang Tang. Realization of Strong Room-Temperature Ferromagnetism in Atomically Thin 2D Carbon Nitride Sheets by Thermal Annealing. ACS Nano 2021, 15, 12069-12076) realized room-temperature ferromagnetism with a high Curie temperature in carbon nitride by annealing treatment to generate nitrogen vacancies, but its saturation magnetization at room temperature was only 0.71 emu / g; this technology is simple and easy to mass-produce, but its product performance is poor, which limits its application in various fields.
[0004] Pin Lyu et al. (Pin Lyu, Ziying Wang, Na Guo, Jie Su, Jing Li, Dongchen Qi, Shibo Xi, Huihui Lin, Qihan Zhang, Stephen J. Pennycook, Jingsheng Chen, Xiaoxu Zhao, Chun Zhang, Kian Ping Loh, and Jiong Lu. Air-Stable Wafer-Scale Ferromagnetic Metallo-Carbon Nitride Monolayer. J. Am. Chem. Soc. 2024, 146, 20604-20614) synthesized air-stable metal-carbon nitride monolayers by low-pressure chemical vapor deposition, which have ultra-dense single magnetic atoms and exhibit room-temperature ferromagnetism. However, the preparation process of this method is relatively complex, with high production costs, and metal elements need to be introduced, making its magnetism vulnerable to the environment and essentially unable to solve the problems of ferromagnetic energy consumption, resources, and pollution. Summary of the Invention
[0005] To overcome the above-mentioned drawbacks in the prior art, the purpose of the present invention is to provide a metal-free carbon-based quantum material with strong room-temperature ferromagnetism and its preparation method. Using high-purity g-C 3 N 4 as the raw material, adsorbed oxygen and structural oxygen are removed through two-step thermal annealing treatment, and then xenon difluoride is used for fluorination in a sealed reaction kettle, and then thermal defluorination is carried out in argon. During the thermal defluorination process, the heptazine structural unit at the edge of fluorinated carbon nitride is broken to form cyano groups while introducing N-C=N bonds, generating dangling bonds; N atoms are lost on the basal plane to form C-C chemical bonds. The reconstruction of both structures enables carbon atoms to generate unpaired spins, thereby introducing local magnetic moments and enhancing ferromagnetic coupling, obtaining a metal-free carbon-based quantum material. This material has the characteristics of high purity, high Curie temperature, and strong room-temperature ferromagnetism. It is a room-temperature non-metal self-polarized permanent magnet, and its performance enables the metal-free carbon-based material to be practically applied in magnetic fields such as aerospace, biomedicine, and spintronics. It is a key material for the research and development of sp electron system carbon-based room-temperature ferromagnetism, which helps the manufacture of lightweight magnetic devices and the application development of spintronic devices and bioelectronic devices; the preparation method of the present invention has the characteristics of simple process and easy repetition.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A preparation method of a metal-free carbon-based quantum material with strong room-temperature ferromagnetism, comprising the following steps:
[0008] Step 1: Calcinate and fluorinate the anaerobic g-C 3 N 4 powder and xenon difluoride in an argon environment, and after naturally cooling to room temperature, open the reaction kettle in an argon environment and let it stand for 1 - 3 h to obtain fluorinated carbon nitride; the mass ratio of the anaerobic g-C 3 N 4 powder to xenon difluoride is 1:(4 - 5);
[0009] Step 2: Perform thermal defluorination on the fluorinated carbon nitride in an argon environment, and after naturally cooling to room temperature, obtain defluorinated carbon nitride;
[0010] Step 3: Magnetize the defluorinated carbon nitride to obtain black powder adsorbed on the surface of the magnet, which is a metal-free carbon-based quantum material with strong room-temperature ferromagnetism.
[0011] The preparation method of the anaerobic g-C 3 N 4 powder is as follows:
[0012] Perform deoxidation annealing on high-purity g-C 3 N 4 powder in an argon environment, and after naturally cooling to room temperature, perform vacuum annealing in a negative pressure environment with a pressure less than 5×10 -4 Pa, and after naturally cooling to room temperature, obtain anaerobic g-C 3 N 4 powder; among them, the deoxidation annealing conditions are: heating to 550 - 650 °C at a rate of 2.5 - 5 °C / min and then holding for 2 - 4 h; the vacuum annealing conditions are: heating to 600 - 650 °C at a rate of 2.5 - 5 °C / min and then holding for 2 - 4 h; in the high-purity g-C 3 N 4 powder, the content of metal elements is less than 0.001%.
[0013] The calcination and fluorination conditions in Step 1 are: heating to 180 - 200 °C at a rate of ≥1 °C / min and then calcining and fluorinating for 24 - 36 h.
[0014] The thermal defluorination conditions in Step 2 are: in argon at 50 - 300 cc / min, heating to 660 - 700 °C at a rate of 20 - 30 °C / min and then holding for 5 - 15 min.
[0015] In Step 3, an electromagnet with a suction density of more than 100 kPa is used to perform magnetic field screening on the magnetized defluorinated carbon nitride to screen out the black powder adsorbed on the surface of the magnet.
[0016] The present invention also provides a metal-free carbon-based quantum material with strong room-temperature ferromagnetism prepared by the above preparation method.
[0017] The structural formula of the metal-free carbon-based quantum material is as follows: , and this structure has a CN chain-like skeleton, C=N bonds, and functional groups of cyano groups; the metal-free carbon-based quantum material is a black powder macroscopically and has a long strip-like crystal morphology or a quadrilateral block crystal morphology microscopically.
[0018] The C:N element ratio of the metal-free carbon-based quantum material is (2.3 - 2.8):1.
[0019] The metal-free carbon-based quantum material has room-temperature ferromagnetism; the saturation magnetization at room temperature is 10.9 - 18.7 emu / g, and the remanent magnetization is 1.7 - 2.6 emu / g; the saturation magnetization at 2K is 15.4 - 25.2 emu / g, and the remanent magnetization is 2.8 - 4.8 emu / g.
[0020] The present invention also provides applications of the above-mentioned metal-free carbon-based quantum material with strong room-temperature ferromagnetism in spintronic devices, bioelectronic devices, and medical detection.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. By subjecting anoxic g-C 3 N 4 to a high-temperature reaction with xenon difluoride and then performing a thermal defluorination treatment in an argon environment, a metal-free carbon-based quantum material with strong room-temperature ferromagnetism is obtained. The heptazine structural unit at the edge of fluorinated carbon nitride is broken, forming cyano groups and N-C=N bonds, generating dangling bonds; while N atoms are lost on the basal plane to form C-C chemical bonds, and the p z orbitals of carbon atoms are in an unsaturated state, both of which provide unpaired spins; the high-density local spins stimulate ferromagnetic coupling between the spins, thus showing strong ferromagnetism at room temperature.
[0023] 2. The metal-free carbon-based quantum materials prepared by the present invention have strong room-temperature ferromagnetism, with a Curie temperature as high as 879.5 K. At a temperature of 2 K, the saturation magnetization is not less than 15.4 emu / g, and can reach up to 25.2 emu / g at most; the remanent magnetization is not less than 2.8 emu / g, and can reach up to 4.8 emu / g at most. At a temperature of 300 K, the saturation magnetization is not less than 10.9 emu / g, and can reach up to 18.7 emu / g at most; the remanent magnetization is not less than 1.7 emu / g, and can reach up to 2.6 emu / g at most. The metal-free carbon-based quantum materials prepared by the preparation method of the present invention have an applicable high Curie temperature and strong room-temperature ferromagnetism, and are a room-temperature non-metal self-polarized permanent magnet, which can replace traditional metal alloy or oxide ferromagnetic materials and be applied in a wide range of magnetic demand scenarios, especially in the fields of aerospace, biomedicine, environmental protection and other fields that require light weight, metal-free, biocompatibility and green degradability. At the same time, it can also be applied in spintronic devices, topological quantum devices and magnetic storage.
[0024] 3. The preparation method of the present invention can prepare an intrinsic carbon-based ferromagnetic material with an applicable high Curie temperature and high magnetization intensity. Compared with the preparation of traditional ferromagnetic materials, the raw materials required for this method are extensive, and g-C 3 N 4 can be prepared from common chemical raw materials such as urea, melamine, dicyandiamide, etc. This method requires extremely low energy consumption, with a maximum thermal annealing temperature of only 700 °C and a short duration. The ferromagnetic material prepared by this method has the characteristics of low density, strong chemical stability and good biocompatibility of carbon-based materials, which are not possessed or difficult to achieve by traditional metal ferromagnetic materials.
[0025] 4. After the high-purity g-C 3 N 4 powder is subjected to two-step thermal annealing treatment, oxygen-free g-C 3 N 4 is obtained, avoiding the non-ferromagnetic impurity phase induced by oxygen elements during the synthesis process, and promoting the formation of a long-range magnetic ordered structure in the metal-free carbon-based quantum materials. The operations of the preparation method of the present invention are all carried out in an argon environment, avoiding the influence of nitrogen, oxygen and water, so that the element ratio in the final product is controllable.
[0026] In summary, the present invention uses high-purity g-C 3 N 4Using [raw material] as the starting material, adsorbed oxygen and structural oxygen are removed through heat treatment. After fluorination with xenon difluoride and subsequent thermal defluorination, a metal-free carbon-based quantum material is obtained. This material has an applicable high Curie temperature and strong room-temperature ferromagnetism. It is a room-temperature non-metal self-polarized permanent magnet and has characteristics such as light weight, chemical stability, and biocompatibility. The raw materials required for the method of the present invention are widely sourced and have extremely low energy consumption. The metal-free carbon-based material obtained by this method can be widely applied in the fields of magnetic applications and quantum information. It is a key material for the research and development of carbon-based room-temperature ferromagnetism in the sp electron system, and is helpful for the applications and development of aerospace, biomedicine, and spintronics. Description of the Drawings
[0027] Figure 1a It is a physical optical photograph of the metal-free carbon-based quantum material prepared in Example 1.
[0028] Figure 1b It is a physical optical photograph of the metal-free carbon-based quantum material prepared in Example 1 when not affected by a magnetic field.
[0029] Figure 1c It is a physical optical photograph of the metal-free carbon-based quantum material prepared in Example 1 being attracted closely by a neodymium iron boron magnet.
[0030] Figure 1d It is a physical optical photograph of the metal-free carbon-based quantum material prepared in Example 1 being attracted distantly by a neodymium iron boron magnet.
[0031] Figure 2a It is an SEM image of the metal-free carbon-based quantum material prepared in Example 1 showing a long strip-like crystal morphology.
[0032] Figure 2b It is an SEM image of the metal-free carbon-based quantum material prepared in Example 1 showing a quadrilateral block-like crystal morphology.
[0033] Figure 3a It is an XPS spectrum of nitrogen in the metal-free carbon-based quantum material prepared in Example 1.
[0034] Figure 3b It is an XPS spectrum of carbon in the metal-free carbon-based quantum material prepared in Example 1.
[0035] Figure 4a It is a full XPS spectrum of the metal-free carbon-based quantum material prepared in Example 1.
[0036] Figure 4b It is a full XPS spectrum of the metal-free carbon-based quantum material prepared in Example 2.
[0037] Figure 5 It is an M-T curve graph of the metal-free carbon-based quantum material prepared in Example 1.
[0038] Figure 6a M-H curve of the metal-free carbon-based quantum material prepared in Example 1 at 2K.
[0039] Figure 6b M-H curve of the metal-free carbon-based quantum material prepared in Example 1 at 300K.
[0040] Figure 7a M-H curve of the metal-free carbon-based quantum material prepared in Example 2 at 2K.
[0041] Figure 7b M-H curve of the metal-free carbon-based quantum material prepared in Example 2 at 300K.
[0042] Figure 8 Magnetic field distribution map of the metal-free carbon-based quantum material powder particles prepared in Example 1 at room temperature and atmosphere. Detailed implementation mode
[0043] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and embodiments.
[0044] The structural formula of the metal-free carbon-based quantum material with strong room-temperature ferromagnetism provided by the present invention is: , this structure has a CN chain-like skeleton, C=N bonds and functional groups of cyano groups; this carbon-based material is a molecular chain with a two-dimensional structure; macroscopically, it appears as black powder and can be attracted by an external magnetic field; microscopically, it has a long strip-like crystal morphology or a quadrilateral block-like crystal morphology, and it is a room-temperature non-metal self-polarized permanent magnet.
[0045] Preparation method of a metal-free carbon-based quantum material with strong room-temperature ferromagnetism, using high-purity g-C 3 N 4 as raw materials, successively carrying out deoxygenation, fluorination, thermal defluorination and magnetization treatments, and all operations are carried out in an argon environment; during the thermal defluorination process, structural reconstruction occurs at the edges and basal planes of the carbon-nitrogen skeleton, introducing a high density of local spins, generating a large number of unpaired spins, thereby exciting ferromagnetic coupling between the spins, and at the same time, the graphite-like phase structure is destroyed to form molecular chains. After screening, a metal-free carbon-based quantum material with strong room-temperature ferromagnetism is obtained; specifically, it includes the following steps:
[0046] Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C 3 N 4The powder is then loaded into a crucible and subsequently transferred to a muffle furnace in an argon atmosphere for deoxidation annealing. It is heated at 2.5 - 5 °C / min to 550 - 650 °C and then held for 2 - 4 h. After natural cooling to room temperature, it is transferred to a tubular furnace filled with argon for vacuum annealing. The air pressure in the tubular furnace is pumped to less than 5×10 -4 Pa by using a vacuum pump, and then heated at 2.5 - 5 °C / min to 600 - 650 °C and held for 2 - 4 h. After natural cooling to room temperature, an oxygen-free g-C 3 N 4 powder is obtained and stored in an argon-filled glove box; in the high-purity g-C 3 N 4 powder used, the content of metal elements shall not be higher than 0.001%; in the present invention, deoxidation annealing is carried out on high-purity g-C 3 N 4 to remove the adsorbed oxygen and structural oxygen in the raw materials and avoid inducing additional non-ferromagnetic impurity phases by oxygen elements during the synthesis process;
[0047] Step 2: In an argon-filled glove box, first place 200 mg of the oxygen-free g-C 3 N 4 powder in the inner lining of a polytetrafluoroethylene reaction kettle, then put 800 - 1000 mg of xenon difluoride, and immediately seal the reaction kettle. Transfer the reaction kettle to a muffle furnace and heat it at ≥1 °C / min to 180 - 200 °C for 24 - 36 h of calcination and fluorination. After natural cooling to room temperature, open the reaction kettle in the argon-filled glove box and let it stand for 1 - 3 h to eliminate side reactions and release the surface residual fluorides, obtaining fluorinated carbon nitride;
[0048] Step 3: In an argon-filled glove box, load the fluorinated carbon nitride into a crucible and then transfer it to a tubular furnace filled with argon for thermal defluorination. Keep the argon in the tubular furnace at 50 - 300 cc / min, heat it at 20 - 30 °C / min to 660 - 700 °C and hold for 5 - 15 min. After natural cooling to room temperature, obtain defluorinated carbon nitride;
[0049] Step 4: Magnetize the defluorinated carbon nitride using a direct current magnetization device, and then use an electromagnet with a suction density ≥100 kPa to attract the magnetized defluorinated carbon nitride. Screen out the un-attracted powder to obtain a metal-free carbon-based quantum material with strong room-temperature ferromagnetism.
[0050] Example 1
[0051] Metal-free carbon-based quantum materials with strong room-temperature ferromagnetism. The metal-free carbon-based quantum materials are molecular chains with a two-dimensional structure, macroscopically presenting as black powder, which can be attracted by an external magnetic field, and microscopically being long-strip crystals or quadrilateral block crystals; the saturation magnetization at room temperature is 18.7 emu / g, and the remanent magnetization is 2.6 emu / g; the saturation magnetization at 2K is 25.2 emu / g, and the remanent magnetization is 4.8 emu / g.
[0052] Preparation method of metal-free carbon-based quantum materials with strong room-temperature ferromagnetism, specifically including the following steps:
[0053] Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C 3 N 4 powder, then load it into a crucible, and then transfer it to a muffle furnace in an argon atmosphere. Heat it to 550 °C at a rate of 2.5 °C / min, keep it warm for 2 h, naturally cool it to room temperature, then transfer it to an argon-filled tube furnace, use a vacuum pump to pump the air pressure in the tube furnace to 2×10 -5 Pa, and then heat it to 600 °C at a rate of 2.5 °C / min and keep it warm for 2 h. After naturally cooling to room temperature, obtain oxygen-free g-C 3 N 4 powder, and store it in an argon-filled glove box;
[0054] Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C 3 N 4 powder in the inner lining of a polytetrafluoroethylene reaction kettle, then put 1000 mg of xenon difluoride, then immediately seal the reaction kettle, transfer the reaction kettle to a muffle furnace, heat it to 180 °C at a heating rate of 5 °C / min, calcine and fluorinate for 36 h, naturally cool it to room temperature, then open the reaction kettle in an argon-filled glove box, and let it stand for 1 h to obtain fluorinated carbon nitride;
[0055] Step 3: In an argon-filled glove box, transfer the fluorinated carbon nitride to a crucible, and then transfer it to an argon-filled tube furnace. Keep the argon in the tube furnace at 50 cc / min, heat it to 660 °C at a rate of 20 °C / min, keep it warm for 15 min, and after naturally cooling to room temperature, obtain de-fluorinated carbon nitride, and store it in the atmospheric environment;
[0056] Step 4: Magnetize the de-fluorinated carbon nitride using a DC magnetization device, then use an electromagnet with a suction density of 100 kPa to attract the magnetized de-fluorinated carbon nitride, and sieve out the un-attracted powder to obtain metal-free carbon-based quantum materials with strong room-temperature ferromagnetism.
[0057] Example 2
[0058] A metal-free carbon-based quantum material with strong room-temperature ferromagnetism. The metal-free carbon-based quantum material is a molecular chain with a two-dimensional structure, macroscopically presenting as black powder and being attracted by an external magnetic field, and microscopically being long-strip-shaped crystals or quadrilateral block-shaped crystals; the saturation magnetization at room temperature is 10.9 emu / g, and the remanent magnetization is 1.7 emu / g; the saturation magnetization at 2K is 15.4 emu / g, and the remanent magnetization is 2.8 emu / g.
[0059] A preparation method of a metal-free carbon-based quantum material with strong room-temperature ferromagnetism, specifically including the following steps:
[0060] Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C 3 N 4 powder, load it into a crucible, and then transfer it to a muffle furnace in an argon atmosphere. Heat it to 650 °C at a rate of 5 °C / min and hold for 4 h. After naturally cooling to room temperature, transfer it to an argon-filled tube furnace. Use a vacuum pump to pump the air pressure in the tube furnace to 5×10 -5 Pa, then heat it to 650 °C at a rate of 5 °C / min and hold for 4 h. After naturally cooling to room temperature, obtain oxygen-free g-C 3 N 4 powder, and store it in an argon-filled glove box;
[0061] Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C 3 N 4 powder in the inner lining of a polytetrafluoroethylene reaction kettle, then put 800 mg of xenon difluoride, and then immediately seal the reaction kettle. Transfer the reaction kettle to a muffle furnace and heat it to 200 °C at a heating rate of 1 °C / min and calcine and fluorinate for 24 h. After naturally cooling to room temperature, open the reaction kettle in an argon-filled glove box and let it stand for 3 h to obtain fluorinated carbon nitride;
[0062] Step 3: In an argon-filled glove box, transfer the fluorinated carbon nitride to a crucible, and then transfer it to an argon-filled tube furnace. Keep the argon gas in the tube furnace at 100 cc / min, heat it to 700 °C at a rate of 30 °C / min and hold for 5 min. After naturally cooling to room temperature, obtain de-fluorinated carbon nitride and store it in the atmospheric environment;
[0063] Step 4: Magnetize the de-fluorinated carbon nitride using a DC magnetization device, and then use an electromagnet with a suction density of 200 kPa to attract the magnetized de-fluorinated carbon nitride. Screen out the un-attracted powder to obtain a metal-free carbon-based quantum material with strong room-temperature ferromagnetism.
[0064] Example 3
[0065] Metal-free carbon-based quantum materials with strong room-temperature ferromagnetism. The metal-free carbon-based quantum materials are molecular chains with a two-dimensional structure, macroscopically presenting as black powder, which can be attracted by an external magnetic field, and microscopically being long-strip crystals or quadrilateral block crystals; the saturation magnetization at room temperature is 13.6 emu / g, and the remanent magnetization is 1.9 emu / g; the saturation magnetization at 2K is 17.1 emu / g, and the remanent magnetization is 3.5 emu / g.
[0066] Preparation method of metal-free carbon-based quantum materials with strong room-temperature ferromagnetism, specifically including the following steps:
[0067] Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C 3 N 4 powder and load it into a crucible, then transfer it to a muffle furnace in an argon atmosphere, heat it to 575 °C at a rate of 3 °C / min and hold for 3 h, naturally cool to room temperature, then transfer it to an argon-filled tube furnace, use a vacuum pump to pump the pressure in the tube furnace to 1×10 -4 Pa, and then heat it to 625 °C at a rate of 3 °C / min and hold for 3 h, naturally cool to room temperature, to obtain oxygen-free g-C 3 N 4 powder, and store it in an argon-filled glove box;
[0068] Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C 3 N 4 powder in the inner lining of a polytetrafluoroethylene reaction kettle, then put 850 mg of xenon difluoride, immediately seal the reaction kettle, transfer the reaction kettle to a muffle furnace, heat it to 185 °C at a heating rate of 10 °C / min and calcine and fluorinate for 27 h, naturally cool to room temperature, then open the reaction kettle in an argon-filled glove box and let it stand for 2 h to obtain fluorinated carbon nitride;
[0069] Step 3: In an argon-filled glove box, transfer the fluorinated carbon nitride to a crucible, then transfer it to an argon-filled tube furnace, keep the argon in the tube furnace at 150 cc / min, heat it to 670 °C at a rate of 23 °C / min and hold for 8 min, naturally cool to room temperature, to obtain de-fluorinated carbon nitride, and store it in the atmospheric environment;
[0070] Step 4: Magnetize the de-fluorinated carbon nitride using a DC magnetization device, then use an electromagnet with a suction density of 300 kPa to attract the magnetized de-fluorinated carbon nitride, and sieve out the un-attracted powder to obtain metal-free carbon-based quantum materials with strong room-temperature ferromagnetism.
[0071] Example 4
[0072] Metal-free carbon-based quantum materials with strong room-temperature ferromagnetism. The metal-free carbon-based quantum materials are molecular chains with a two-dimensional structure, macroscopically presenting as black powder, which can be attracted by an external magnetic field, and microscopically being long-strip crystals or quadrilateral block crystals; the saturation magnetization at room temperature is 15.4 emu / g, and the remanent magnetization is 2.3 emu / g; the saturation magnetization at 2K is 19.3 emu / g, and the remanent magnetization is 3.9 emu / g.
[0073] Preparation method of metal-free carbon-based quantum materials with strong room-temperature ferromagnetism, specifically including the following steps:
[0074] Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C 3 N 4 powder and load it into a crucible, then transfer it to a muffle furnace in an argon atmosphere, heat it to 600 °C at a rate of 4 °C / min and hold for 3.5 h, naturally cool to room temperature, then transfer it to an argon-filled tube furnace, use a vacuum pump to pump the air pressure in the tube furnace to 3×10 -4 Pa, and then heat it to 610 °C at a rate of 4 °C / min and hold for 3.5 h, naturally cool to room temperature, to obtain oxygen-free g-C 3 N 4 powder, and store it in an argon-filled glove box;
[0075] Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C 3 N 4 powder in the inner lining of a polytetrafluoroethylene reaction kettle, then put 900 mg of xenon difluoride, then immediately seal the reaction kettle, transfer the reaction kettle to a muffle furnace, heat it to 190 °C at a heating rate of 8 °C / min and calcine and fluoridate for 30 h, naturally cool to room temperature, then open the reaction kettle in an argon-filled glove box and let it stand for 1.5 h to obtain fluorinated carbon nitride;
[0076] Step 3: In an argon-filled glove box, transfer the fluorinated carbon nitride to a crucible, then transfer it to an argon-filled tube furnace, keep the argon gas in the tube furnace at 200 cc / min, heat it to 680 °C at a rate of 25 °C / min and hold for 10 min, naturally cool to room temperature, to obtain de-fluorinated carbon nitride, and store it in the atmospheric environment;
[0077] Step 4: Magnetize the de-fluorinated carbon nitride using a DC magnetization device, then use an electromagnet with a suction density of 400 kPa to attract the magnetized de-fluorinated carbon nitride, and sieve out the un-attracted powder to obtain metal-free carbon-based quantum materials with strong room-temperature ferromagnetism.
[0078] Example 5
[0079] Metal-free carbon-based quantum materials with strong room-temperature ferromagnetism. The metal-free carbon-based quantum materials are molecular chains with a two-dimensional structure, macroscopically presenting as black powder, which can be attracted by an external magnetic field, and microscopically being long-strip crystals or quadrilateral block crystals; the saturation magnetization at room temperature is 16.6 emu / g, and the remanent magnetization is 2.1 emu / g; the saturation magnetization at 2K is 22.5 emu / g, and the remanent magnetization is 4.3 emu / g.
[0080] Preparation method of metal-free carbon-based quantum materials with strong room-temperature ferromagnetism, specifically including the following steps:
[0081] Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C 3 N 4 powder and load it into a crucible, then transfer it to a muffle furnace in an argon atmosphere, heat it to 625 °C at a rate of 3.5 °C / min and hold for 2.5 h, naturally cool to room temperature, then transfer it to an argon-filled tube furnace, use a vacuum pump to pump the pressure in the tube furnace to 5×10 -4 Pa, and then heat it to 640 °C at a rate of 3.5 °C / min and hold for 2.5 h, naturally cool to room temperature, to obtain oxygen-free g-C 3 N 4 powder, and store it in an argon-filled glove box;
[0082] Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C 3 N 4 powder in the inner lining of a polytetrafluoroethylene reaction kettle, then put 950 mg of xenon difluoride, immediately seal the reaction kettle, transfer the reaction kettle to a muffle furnace, heat it to 195 °C at a heating rate of 3 °C / min and calcine and fluorinate for 33 h, naturally cool to room temperature, then open the reaction kettle in an argon-filled glove box and let it stand for 2.5 h to obtain fluorinated carbon nitride;
[0083] Step 3: In an argon-filled glove box, transfer the fluorinated carbon nitride to a crucible, then transfer it to an argon-filled tube furnace, keep the argon in the tube furnace at 300 cc / min, heat it to 690 °C at a rate of 28 °C / min and hold for 13 min, naturally cool to room temperature, to obtain de-fluorinated carbon nitride, and store it in the atmospheric environment;
[0084] Step 4: Magnetize the de-fluorinated carbon nitride using a DC magnetization device, then use an electromagnet with a suction density of 500 kPa to attract the magnetized de-fluorinated carbon nitride, and sieve out the un-attracted powder to obtain metal-free carbon-based quantum materials with strong room-temperature ferromagnetism.
[0085] The metal-free carbon-based quantum materials with strong room-temperature ferromagnetism prepared in the above examples can all be applied in spin electronic devices, bioelectronic devices and medical detections.
[0086] As shown Figure 1a in Figure 1, the metal-free carbon-based quantum material prepared in Example 1 is a black powder; Figure 1b Figure 2 shows the state of the metal-free carbon-based quantum material prepared in Example 1 without being affected by a magnetic field, Figure 1c Figure 3 shows that the metal-free carbon-based quantum material prepared in Example 1 is attracted by a neodymium iron boron magnet at a short distance, Figure 1d Figure 4 shows that the metal-free carbon-based quantum material prepared in Example 1 is attracted by a neodymium iron boron magnet at a long distance, intuitively proving that the metal-free carbon-based quantum material prepared in Example 1 has strong room-temperature ferromagnetism.
[0087] As shown Figure 2a in Figure 2b Figures 5 and 6, it can be seen from the SEM images that the metal-free carbon-based quantum material prepared in Example 1 is in the form of long strip crystals or quadrilateral block crystals, conforming to the crystal characteristics of a chain-like molecular structure.
[0088] As shown Figure 3a in Figure 3b Figures 7 and 8, the metal-free carbon-based quantum material prepared in Example 1 contains chemical bonds in different states, that is, NC 3 , C-N=C, N=C-N and a large number of C-C bonds coexist, revealing that the graphite-like phase structure is broken and a chain-like structure is formed.
[0089] As shown Figure 4a in Figure 9, the ratio of C element to N element in the metal-free carbon-based quantum material prepared in Example 1 is 2.8:1; as shown Figure 4b in Figure 10, the ratio of C element to N element in the metal-free carbon-based quantum material prepared in Example 2 is 2.3:1; indicating that the metal-free carbon-based quantum material loses a large number of nitrogen atoms relative to g-C 3 N 4 .
[0090] As shown in Table 1, there is no presence of any magnetic metal at a concentration of one part per million (the precision of ICP-OES) in the metal-free carbon-based quantum material prepared in Example 1, proving that the ferromagnetism of the metal-free carbon-based quantum material is an intrinsic property.
[0091] Table 1 ICP-OES results of the metal-free carbon-based quantum material prepared in Example 1
[0092]
[0093] As shown Figure 5 in Figure 11, the M-T curve of the metal-free carbon-based quantum material prepared in Example 1 under an external magnetic field of 1000 Oe shows that the saturation magnetization rapidly decreases at 879.5 K, indicating that the metal-free carbon-based quantum material has ferromagnetism and the Curie temperature is 879.5 K.
[0094] As shownFigure 6a As shown, the saturation magnetization of the metal-free carbon-based quantum material prepared in Example 1 at 2K M S is 25.16 emu / g, and the remanent magnetization M r is 4.82 emu / g, and the coercive field H C is 553 Oe; as Figure 6b shown, the saturation magnetization at 300K M S is 18.72 emu / g, and the remanent magnetization M r is 2.59 emu / g, and the coercive field H C is 233 Oe; compared with existing two-dimensional carbon-based materials, the metal-free carbon-based quantum material prepared in the present invention has a high saturation magnetization and has magnetic properties that can be practically applied at room temperature.
[0095] As Figure 7a shown, the saturation magnetization of the metal-free carbon-based quantum material prepared in Example 2 at 2K M S is 15.4 emu / g, and the remanent magnetization M r is 2.79 emu / g, and the coercive field H C is 562 Oe; as Figure 7b shown, the saturation magnetization at 300K M S is 10.9 emu / g, and the remanent magnetization M r is 1.69 emu / g, and the coercive field H C is 300 Oe; compared with existing two-dimensional carbon-based materials, it shows that the metal-free carbon-based quantum material prepared in the present invention has a high saturation magnetization and has magnetic properties that can be practically applied at room temperature.
[0096] As Figure 8 shown, the 500-nm particle size agglomerated powder of the metal-free carbon-based quantum material prepared in Example 1 in a room temperature atmospheric environment has obvious NS magnetic poles, proving that the metal-free carbon-based quantum material prepared in the present invention is a permanent magnet with spontaneous magnetization characteristics at room temperature.
Claims
1. A method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism, characterized in that: The following steps are involved: Step 1: calcining and fluorinating oxygen-free g-C3N4 powder and xenon difluoride sealed in a reaction kettle in an argon environment, opening the reaction kettle in an argon environment after natural cooling to room temperature, and standing for 1-3 hours to obtain fluorinated carbon nitride; the mass ratio of the oxygen-free g-C3N4 powder to xenon difluoride is 1: (4-5); Step 2: thermally defluorinating the fluorinated carbon nitride in an argon environment, and naturally cooling to room temperature to obtain defluorinated carbon nitride; Step 3: Magnetize the defluorinated carbon nitride to obtain a black powder adsorbed on the surface of the magnet, which is a metal-free carbon-based quantum material with strong room temperature ferromagnetism.
2. The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 1, characterized in that: The preparation method of the oxygen-free g-C3N4 powder is: The high-purity g-C3N4 powder was deoxidized and annealed in an argon environment, and then cooled to room temperature under a pressure of less than 5×10 -4 Pa in a negative pressure environment, and then naturally cool to room temperature to obtain oxygen-free g-C3N4 powder; wherein, the deoxygenation annealing conditions are: heating to 550-650°C at 2.5-5°C / min and then keeping warm for 2-4h; the vacuum annealing conditions are: heating to 600-650°C at 2.5-5°C / min and then keeping warm for 2-4h; the content of metal elements in the high-purity g-C3N4 powder is less than 0.001%.
3. The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 1, characterized in that: The calcination and fluorination conditions in step 1 are: heating to 180-200° C. at a rate of ≥1° C. / min and then calcining and fluorinating for 24-36 hours.
4. The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 1, characterized in that: The thermal defluorination conditions in step 2 are: in 50-300cc / min argon, heating to 660-700°C at 20-30°C / min and then keeping the temperature for 5-15 minutes.
5. The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 1, characterized in that: In the step 3, an electromagnet with a suction density of at least 100 kPa is used to perform magnetic field screening on the defluorinated carbon nitride after magnetization treatment, so as to screen out the black powder adsorbed on the surface of the magnet.
6. A metal-free carbon-based quantum material with strong room temperature ferromagnetism obtained according to the preparation method according to any one of claims 1 to 5.
7. The metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 6, characterized in that: The structural formula of the metal-free carbon-based quantum material is: The structure has a CN chain skeleton, a C=N bond and a cyano functional group; the metal-free carbon-based quantum material is a black powder at the macroscopic level and a long strip crystal morphology or a quadrilateral block crystal morphology at the microscopic level.
8. The metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 6, characterized in that: The C:N element ratio of the metal-free carbon-based quantum material is (2.3-2.8):
1.
9. The metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 6, characterized in that: The metal-free carbon-based quantum material has room temperature ferromagnetism; the saturation magnetization at room temperature is 10.9-18.7emu / g, and the residual magnetization is 1.7-2.6emu / g; the saturation magnetization at 2K is 15.4-25.2emu / g, and the residual magnetization is 2.8-4.8emu / g.
10. Use of the metal-free carbon-based quantum material with strong room temperature ferromagnetism as claimed in any one of claims 7 to 9 in bioelectronic devices.
Citation Information
Patent Citations
Preparation method for ferromagnetic B-doped g-C3N4 two-dimensional ultrathin nanosheet
CN106006583A
Carbon-based confinement interface supported palladium monatomic catalyst and preparation method thereof
CN111659444A